A study on the microbiological and angiogenic properties of burn injuries treated with tualang honey versus silver based dressing - Halim, Ahmad Sukari; Dorai, Ananda Aravazhi; Sulaiman, Wan Azman Wan (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Tualang honey was demonstrated to pose substantial bactericidal as well as bacteriostatic effect. The Aquacel dressing soaked with pure Tualang honey without any dilution was less sticky than manuka and was easier to apply as a dressing.